Correlation Between Serum Procollagen Type 1 N-Terminal Propeptide Level With Modified Rodnan Skin Score In Systemic Sclerosis Patients. - Vincent, Vincent; Dewi, Sumartini; Wachjudi, Rachmat Gunadi (Indonesian Rheumatology Association, 2017)
Introduction: Systemic Sclerosis (SSc) is a chronic autoimmune disease, characterized by vasculopathy, specific autoimmune, and fibrosis. Assesment of skin fibrosis by modified Rodnan Skin Score (mRSS) can not detect the minimal changes of skin fibrosis within lessthan 3 months. A biomarker is needed to assess the minimal changes of skin fibrosis progressivity with a more objective, quantitative, and rapid way. Procollagen type-1 N-Terminal Propeptide (P1NP), a degradation product of collagen type-1, may become a potential biomarker for skin fibrosis. This study aims to evaluate the correlation between skin fibrosis by mRSS with P1NP serum in systemic sclerosis.Methods: This was a cross-sectional study performed among systemic sclerosis patients at Rheumatology outpatient clinic, Dr.Hasan Sadikin Hospital Bandung, from May 2016 to July 2016. Skin fibrosis was measured by mRSS. P1NP level was determined by ELISA. Data were analyzed using Rank-Spearman Correlation.Result: There were thirty-seven subjects, with mean age 37 (SD Â±7) years old. Most of subjects were female (91.9%). Subjects consisted of 23 (62.2%) limited SSc and 14 (37.8%) diffuse SSc. Six subjects (16.2%) were DMARD naÃ¯ve. We found median (range) P1NP serum was 43.85 (9.81-127.90) ng/dL, while the median of MRSS was 14 (3-36). There is a moderate correlation between MRSS and P1NP serum (r=0.443, p=0.003)Conclusion: There was a significant correlation between mRSS and P1NP serum in systemic sclerosis patient at Dr. Hasan Sadikin Hospital Bandung.Keywords: systemic sclerosis, P1NP, modified rodnan skin score